LITERASI DIGITAL DAN PEMBUATAN APLIKASI ASPIRASI UNTUK FORUM ANAK DESA PEJENGKOLAN - Maarif, Vadlya; Syukron, Akhmad; Kiswati, Sri; Anajib, Barra Rifki; Putranto, Restu Ardi; Pramono, Dhorifa Habibie Yute; Anggita, Christina Yuli (Jurnal Abdi Insani, 2025)
This community service activity was motivated by the low level of digital literacy and limited participation of children in village development, especially in rural areas such as Pejengkolan Village. The aim of this activity is to improve the digital literacy of children and adolescents and to provide a digital aspiration platform to encourage their involvement in village development. The program was carried out in three main stages: partner engagement through focus group discussions (FGD) and surveys, implementation of training and application development, and evaluation through pre-test and post-test. The results showed a significant increase in understanding among children and parents regarding digital literacy, personal data security, and safe internet usage. Additionally, the Pejengkolan Village Children's Forum now has a digital platform in the form of a website (https://forumanakpejengkolan.web.id/) that serves as a medium for expressing aspirations and documenting their activities. The evaluation through pre-test and post-test demonstrated an increase in knowledge by 80–90% on several key indicators such as digital ethics, personal data protection, and digital footprints. This activity made a tangible contribution to shaping a digitally literate, ethical, and actively engaged young generation in village development